Balancing benefits and risks of tiktok use: Impacts on children’s cognitive, social-emotional development and digital well-being - Desak Putu Suciwati; Gusti Putu Anom Priadita; Qinghao Wu; Norhayati Mohd Yusof; Aondowase Saawuan (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2026)
This paper examines the impact of TikTok use among children, focusing on development, behaviour, and digital well-being. The aims are to (1) identify cognitive, social-emotional, and behavioural effects, (2) distinguish positive from negative outcomes, and (3) highlight the role of adult mediation. Using a qualitative literature review of empirical and narrative studies on early childhood and primary school pupils, data are synthesized from classroom observations, interviews, and thematic and content analyses reported in prior research. Analysis clusters findings into educational/cognitive benefits, creativity and self-expression, mental health and behavioural risks, and conditions under which TikTok supports healthy development. Evidence indicates that TikTok can foster creativity, self-confidence, informal learning, and social connection when use is moderate and content is appropriate. However, excessive or unsupervised use is associated with attentional problems, reduced learning focus, social withdrawal, exposure to inappropriate content, poor time management, and signs of digital addiction. The conclusion emphasizes structured limits, active parental and teacher guidance, and digital literacy education to maximize benefits and mitigate harms.